Essential elements of a community empowerment approach to HIV prevention among female sex workers engaged in Project Shikamana in Iringa, Tanzania - Leddy, Anna M. (Cult Health Sex, 2019)
Globally, female sex workers bear a disproportionate burden of HIV, with those in sub-Saharan Africa being among the most affected. Community empowerment approaches have proven successful at preventing HIV among this population. These approaches facilitate a process whereby sex workers take collective ownership over programmes to address the barriers they face in accessing their health and human rights. Limited applications of such approaches have been documented in Africa. We describe the community empowerment process among female sex workers in Iringa, Tanzania, in the context of a randomised controlled trial of a community empowerment-based model of combination HIV prevention. We conducted 24 in-depth interviews with participants from the intervention community and 12 key informant interviews with HIV care providers, police, venue managers, community advisory board members and research staff. Content analysis was employed, and salient themes were extracted. Findings reveal that the community empowerment process was facilitated by the meaningful engagement of sex workers in programme development, encouraging sex worker ownership over the programme, providing opportunities for solidarity and capacity building, and forming partnerships with key stakeholders. Through this process, sex workers mobilised their collective agency to access their health and human rights including HIV prevention, care and treatment.